Plaque vulnerability and thrombus formation according to area stenosis in chronic stable angina - Eun-Seok Shin; Jun-Hyok Oh; Chang-Wook Nam; Bon-Kwon Koo (Scientific Reports)
Abstract The relationship between luminal stenosis severity and plaque vulnerability in chronic stable angina (CSA) is not well studied. This study aimed to investigate the link between stenosis severity, plaque characteristics, and thrombus prevalence in CSA patients using optical coherence tomography. The 174 lesions (146 patients) with CSA divided into three groups according to the percentage of area stenosis (AS); group A (AS < 50%), group B (50% ≤ AS < 70%), and group C (AS ≥ 70%). Twenty-four lesions of group A, 51 lesions of group B, and 99 lesions from group C were studied. The prevalence of thrombus was 19.0% and it was significantly different among the three groups (none in group A vs. 17.6% in group B vs. 24.2% in group C; P = 0.024). The more severe the luminal narrowing, the more thrombus occurred, with a higher prevalence at the minimal lumen area site. Additionally greater the area stenosis, the higher the prevalence of lipid-rich plaque, thin cap plaque, macrophage infiltration, and ruptured plaque. In the multivariate analysis, thrombus was independently associated with ruptured plaque (OR = 20.96, CI 8.40–57.69, P < 0.001), macrophage infiltration (OR = 3.77, CI 1.53–10.72, P = 0.007), lipid angle (OR = 1.01, CI 1.00–1.01, P = 0.004), and area stenosis (OR = 1.05, CI 1.02–1.10, P = 0.002). In patients with CSA, the prevalence of thrombus, as assessed by OCT, is not uncommon. Plaque vulnerability, including thrombus occurrence, increased with the severity of area stenosis and was more prevalent at the minimal lumen site exposed to high shear stress.